2001
DOI: 10.1016/s0550-3213(01)00220-6
|View full text |Cite
|
Sign up to set email alerts
|

Brane mediated supersymmetry breaking

Abstract: We propose a mechanism for mediating supersymmetry breaking in Type I string constructions. in gaugino mediated models, the gauginos and Higgs doublets receive direct soft masses from the source brane, and flavour-changing neutral currents are naturally suppressed since the first and second family squarks and sleptons receive suppressed soft masses. However, unlike the gaugino mediated model, the third family squarks and sleptons receive unsuppressed soft masses, resulting in a very distinctive spectrum with h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 38 publications
2
29
0
Order By: Relevance
“…In this paper we extend our previous analysis of the non-universal MSSM to a semi-realistic type I string theory model of the form originally proposed in [4] and phenomenologically analysed in [5] (see also [6], [7], [8], [9]). Using such a string model we can address two questions.…”
Section: Introductionmentioning
confidence: 62%
“…In this paper we extend our previous analysis of the non-universal MSSM to a semi-realistic type I string theory model of the form originally proposed in [4] and phenomenologically analysed in [5] (see also [6], [7], [8], [9]). Using such a string model we can address two questions.…”
Section: Introductionmentioning
confidence: 62%
“…[24] demonstrated that the SS effects are always present, and a vanishing SS parameter at tree-level will be generated at 1-loop by bulk supergravity fields 15 . In the case that SUSY breaking is localized on a hidden sector brane, the SS breaking parameter ω SS is no longer discrete, but may take a range of values that depend upon the relative strength of the SUSY breaking and the matter content of fields living in the extra dimension 16 . In our model, the third family and Higgs hypermultiplets (N H = 19) live in the bulk with the MSSM vector multiplets (N V = 12), and the SS breaking parameter tends towards ω SS = 0 (ω SS = 1/2) for weak (strong) SUSY breaking on the brane which is equivalent to minimal (maximal) mixing in the stop sector.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…1 obtained from the charged lepton masses in Eq. (42), and v and m SUSY represent the Higgs VEV, v ≃ 174 GeV, and the mass scale of supersymmetry breaking parameters, respectively. Note that these mass insertion parameters do not depend on tan β, in contrast to many supersymmetric models where the µ → e transition amplitude is proportional to tan β.…”
Section: Impact On Flavor Physicsmentioning
confidence: 99%